Advanced oxidation of the commercial nonionic surfactant octylphenol polyethoxylate Triton™ X-45 by the persulfate/UV-C process: effect of operating parameters and kinetic evaluation - Arslan-Alaton, Idil; Olmez-Hanci, Tugba; Genc, Bora; Dursun, Duygu (Frontiers in Chemistry, 2013)
This study explored the potential use of a sulfate radical (SO4●-)-based photochemical oxidation process to treat the commercial nonionic surfactant octylphenol polyethoxylate (OPPE) TritonTMX-45. For this purpose, the effect of initial S2O82- (0-5.0 mM) and OPPE (10-100 mg/L) concentrations on OPPE and its organic carbon content (TOC) removal were investigated at an initial reaction pH of 6.5. Results indicated that very fast OPPE degradation (100%) accompanied with high TOC abatement rates (90%) could be achieved for 10 and 20 mg/L aqueous OPPE at elevated S2O82- concentrations (>2.5 mM). S2O82-/UV-C treatment was still capable of complete OPPE removal up to an initial concentration of 40 mg/L in the presence of 2.5 mM S2O82-. On the other hand, TOC removal efficiencies dropped down to only 40% under the same reaction conditions. S2O82-/UV-C oxidation of OPPE was also compared with the relatively well-known and established H2O2/UV-C oxidation process. Treatment results showed that the performance of S2O82-/UV-C was comparable to that of H2O2/UV-C oxidation for the degradation and mineralization of OPPE. In order to elucidate the relative reactivity and selectivity of SO4●- and HO●, bimolecular reaction rate coefficients of OPPE with SO4●- and HO● were determined by employing competition kinetics with aqueous phenol (47 M) selected as the reference compound. The first-order abatement rate coefficient obtained for OPPE during S2O82-/UV-C oxidation (0.044 min-1) was found to be significantly lower than that calculated for phenol (0.397 min-1). In the case of H2O2/UV-C oxidation however, similar first-order abatement rate coefficients were obtained for both OPPE (0.087 min-1) and phenol (0.140 min-1). Second-order reaction rate coefficients for OPPE with SO4●- and HO● were determined as 9.8108 M-1s-1 and 4.1109 M-1s-1, respectively. The kinetic study also revealed that the selectivity of SO4●- was found to be significantly higher than that of HO●.